Volume 2A: Turbomachinery 2014
DOI: 10.1115/gt2014-25766
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Effects of Bowed Blade on the Flow Field in a Cantilevered Stator Passage

Abstract: This paper presents experimental investigation conducted on a 2-stage low speed axial research compressor with cantilevered stator vanes. Flow fields at four different axial locations in the radial stacking and bowed stator passage were measured at maximum flow point and near stall point using 4 five-hole pressure probes. The aim of the work is to study the effects of the bowed stators with hub clearance on the flow field of compressor blade passage. The investigations were conducted with the first stage of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Many studies [10][11][12][13][14] have shown that curved blades which have been matched reasonably well have good results in restraining the flow separation. At present the amount of researches concerning the transition phenomenon in curved compressor cascades is small.…”
Section: Introductionmentioning
confidence: 97%
“…Many studies [10][11][12][13][14] have shown that curved blades which have been matched reasonably well have good results in restraining the flow separation. At present the amount of researches concerning the transition phenomenon in curved compressor cascades is small.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, non-uniform clearance is also used to control the loss. 12 Other effective methods to control the loss caused by the hub leakage flow are to adopt bowed [13][14][15][16][17] and forward end-sweep 18,19 cantilevered stator design to improve the flow field near the hub. In this paper, the cantilevered stator adopts positive bowed and fore-sweep three-dimensional design of the fore-loaded blade near the hub region to control the loss.…”
Section: Introductionmentioning
confidence: 99%
“…George et al 25 applied the end-bend on stators and they found that the hub loading of the blade was improved with the smaller secondary flow. Luo et al 26 conducted an experimental investigation on the 2-stage compressor with bowed cantilevered stators and the leakage vortex, corner stall and passage cross flow were eliminated obviously.…”
Section: Introductionmentioning
confidence: 99%